Incidence and Outcomes of Re-Exploration in Adult Cardiac Surgery at A Tertiary Care Hospital - Pradhan, Ashok; Pokharel, Rojina; Kadel, Prashiddha B; Bashyal, Krishnaprashad; Khakurel, Prabhat; Baral, Ravi K; Bhattarai, Anil; Koirala, Bhagawan (Journal of Institute of Medicine Nepal, 2023)
Introduction: Postoperative bleeding is a significant complication following cardiac surgery, with a global re-exploration incidence of 2-5%. This study aims to investigate re-exploration rates, risk factors, and outcomes within the unique context of a tertiary care center in Nepal. Methods: In this retrospective, single-center study, we analyzed all consecutive adult patients (≥18 years) who underwent cardiac surgery with cardiopulmonary bypass (CPB) at the Manmohan Cardiothoracic Vascular and Transplant Centre (Nepal) between 2018-2021. Data on demographics, clinical characteristics, operative details, re-exploration, and outcomes were extracted from medical records. Statistical analysis included descriptive statistics, chi-square tests, independent samples t-tests, and logistic regression. Results: Of 720 patients, 56 (7.8%) required re-exploration for bleeding. Emergency procedures were strongly associated with higher re-exploration (p<0.05). Non-surgical bleeding was the primary cause in 42.9% of cases. Independent risk factors included preoperative deranged LFTs (OR=2.1, 95% CI: 1.2-3.7), elevated creatinine (>1.5 mg/dL, OR= 3.2, 95% CI: 1.8-5.6), prolonged CPB time (>120 min), and substantial transfusion requirements. Modified Bentall's procedures had the highest re-exploration rate (21.4%). Re-explored patients experienced higher AKI rates (87.5%), longer hospitalizations (13.6 vs. 7.2 days, p<0.001), and increased in-hospital mortality confined to emergency cases (1.94%). Conclusion: Emergency procedures had higher rate of re-exploration. Preoperative deranged LFTs, elevated creatinine, prolonged CPB time, and substantial transfusion requirements were independent risk factors for re-exploration. Re-explored cases experienced higher complication. In-hospital mortality were confined to emergency cases only.